Changes in bone mineral density over 10 years in patients with early rheumatoid arthritis. Issue 1 (11th February 2020) - Theander, Lisa; Willim, Minna; Nilsson, Jan Åke; Karlsson, Magnus; Åkesson, Kristina E; Jacobsson, Lennart T H; Turesson, Carl
Abstract : Objectives: To investigate changes in bone mineral density (BMD) in patients with early rheumatoid arthritis (RA) over a 10-year period. Methods: Consecutive patients with early RA (symptom duration <12 months) were followed according to a structured programme and examined with dual-energy X-ray absorptiometry (DXA) at inclusion and after 2, 5 and 10 years. Mean Z-scores over the study period were estimated using mixed linear effect models. Changes in Z-scores between follow-up visits were analysed using paired T-tests. Results: At inclusion, 220 patients were examined with DXA. At the femoral neck, the mean Z-score over 10 years was −0.33 (95 % CI −0.57 to −0.08) in men and −0.07 (−0.22 to 0.08) in women. Men had significantly lower BMD at the femoral neck than expected by age at inclusion (intercept Z-score value −0.35; 95 % CI −0.61 to −0.09), whereas there was no such difference in women. At the lumbar spine, the mean Z-score over the study period for men was −0.05 (−0.29 to 0.19) and for women 0.06 (−0.10 to 0.21). In paired comparisons of BMD at different follow-up visits, femoral neck Z-scores for men decreased significantly from inclusion to the 5-year follow-up. After 5 years, no further reduction was seen. Conclusions: In this observational study of a limited sample, men with early RA had reduced femoral neck BMD at diagnosis, with a further significant but marginal decline during the first 5 years. Lumbar spine BMD Z-scores were not reduced in men or women with early RA. Data on 10-year follow-up were limited.